Analisys Of Total Fishery Production In Sukabumi District Using Non-Linear Regression Method - Ramadhani, Ar Reemuna Rizqandaru; Muzzaki, Ahmad; Firmansyah, Bagus; Rangga, Muhammad; Juansyah, Panji (Universitas Syiah Kuala, 2023)
One area that has the potential for capture fisheries and aquaculture in Indonesia is Sukabumi Regency. This study analyzes the amount of fishery production in Sukabumi Regency using non-linear regression methods. The data used in this research is fishery catch production data from the Palabuhanratu Archipelago Fishing Port during 2020-2022. The results of this study show variations in fishery production from month to month in 2020-2022. This research makes an important contribution in understanding the factors that influence fishery production, so that it is hoped that it can help manage fishery resources and develop the fishery sector in a sustainable manner in Sukabumi Regency. This study has the main objective, namely to identify significant environmental factors in influencing the amount of fisheries production in Sukabumi Regency. Based on the graph and the percentage of total fishery production in the 2020-2022 range in Sukabumi Regency, there are several things that need attention, such as a decrease in the amount of fishery production in 2022. Nusantara Fisheries (PPN) Palabuhanratu, Sukabumi Regency.